Endomorphisms of Cayley digraphs of rectangular groups - Arworn, S.; Gyurov, B.; Nupo, N.; Panma, S. (Algebra and Discrete Mathematics, 2018)
Let Cay(S,A) denote the Cayley digraph of the semigroup S with respect to the set A, where A is any subset of S. The function f : Cay(S,A) → Cay(S,A) is called an endomorphism of Cay(S,A) if for each (x, y) ∈ E(Cay(S,A)) implies (f(x), f(y)) ∈ E(Cay(S,A)) as well, where E(Cay(S,A)) is an arc set of Cay(S,A). We characterize the endomorphisms of Cayley digraphs of rectangular groups G × L × R, where the connection sets are in the form of A = K × P × T.